Reduction/elimination erasure line in voice coil motor assembly - Chen, Man (2014)
Because of Hard Disk Drive miniaturization, even smallest particle contamination can damage the whole Drive. In this project, the “erasure line method” is used to measure the magnetic contamination level of certain Hard Disk Drive components. Hence, the objective of the project was to reduce or eliminate erasure lines in Voice Coil Motor Assembly (VCMA). The project started off with the investigation and analysis of the erasure line method itself. Using these results the sources that generate erasure lines can then be determined. They are the magnetic particles from the components themselves and also the processes which cause scratches on the components. Subsequently, thorough investigations were done on production lines to identify the processes that can be the source of the particles. Particle identifications for every suspected process were the next thing done in the project. The identifications were then done using Scanning Electron Microscope/ Energy Dispersive X-ray machine. Finally some suggested solutions, which are putting cushion to the equipments and extra cleaning steps, were formulated. To make the project complete, the solution testing was carried out on the production line. However, due to time limitations, only one solution testing, which is the most feasible to be implemented is described.